Hi

I found a proof, but can not follow. The critical part is the following:

$\displaystyle \mathbb{E}\left[\frac 1 n \sum_{i=1}^n x_i \left(1-\frac 1 n \sum_{i=1}^n w_i +\left(\frac 1 n \sum_{i=1}^n w_i\right)^2-\left(\frac 1 n \sum_{i=1}^n w_i\right)^3+...\right)\right]-X$

where

$\displaystyle \mathbb{E}\left[x_i\right]=X, \mathbb{E}\left[w_i\right]=0$

I need an approximation / upperbound to n. The authors assert that it is in order of $\displaystyle n^{-1}$. Can anyone explain it?

Thanking you in anticipation!